Topoisomerase II alpha mRNA and tumour cell proliferation in non-Hodgkin's lymphoma. Issue 1 (January 1997) - Lohri, A; Reuter, J; Gudat, F; Herrmann, R
Abstract : AIMS: To elucidate potential mechanisms of drug resistance, levels of topoisomerase II alpha mRNA, a target for cytostatic drugs, were measured in cryopreserved tumour tissue from 36 patients with non-Hodgkin's lymphoma. To evaluate the potential association between topoisomerase II alpha and cell proliferation, Ki-67 immunostaining was also assessed. METHODS: The study population comprised 13 patients with low grade and 20 with high grade non-Hodgkin's lymphoma. Three patients had recurrent disease. Topoisomerase II alpha mRNA was quantitated by using reverse transcription polymerase chain reaction (RT-PCR) and the PCR product measured by using HPLC. The MIB-1 monoclonal antibody was used for Ki-67 immunostaining. RESULTS: Levels of topoisomerase II alpha mRNA correlated strongly with the Ki-67 labelling index and were higher in high grade than in low grade lymphomas. Patients in complete clinical remission of high grade lymphoma had a higher Ki-67 labelling index and tended to have higher topoisomerase II alpha mRNA levels. CONCLUSIONS: Although topoisomerase II alpha mRNA levels may be indicative of sensitivity to drugs, it is more likely that they reflect the proliferation status of the cell, which in turn involves a large number of additional molecular systems that influence response to treatment.